Development and Conflict Resolution: A Social Capital Approach to Post-Conflict Redevelopment - Dixon, Lawrence G. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This paper presents an approach for integrating conflict resolution with development by making use of a better understanding of social capital. Development is reviewed and argued to be rooted in colonialism, and as such has serious limitations which hinder its overall effectiveness for civil society. A model of social capital is constructed and explained. Then, conflict resolution is introduced and demonstrated to be trust building. It is compared with development and is shown to complement its shortcomings. Conflict resolution as procedural infrastructure is introduced. Finally, a discussion of how development and conflict resolution fit into the social capital model is presented